Advances in biomaterials for osteonecrosis treatment - Wang, Dapeng; Li, Jiannan; Liu, Yu; Wang, Shuaishuai; Duan, Shuo; Liu, Zhiyang; Li, Shuaiwei; Liang, Jun; Meng, Guangwei; Zhang, Minglei (Frontiers in Pharmacology, 2025)
Osteonecrosis, or ischemic osteonecrosis, occurs when bone tissue dies due to a reduced blood supply. This process begins with the death of osteocytes and is followed by the development of necrotic bone tissue. The body initiates intrinsic repair mechanisms to counteract osteonecrosis. However, insufficient blood supply and poor osteogenic microenvironments often lead to suboptimal outcomes Treatment of osteonecrosis is focused on controlling symptoms, especially pain, and preserving the function of the affected bone. In severe cases, joint replacement may be required. For early-stage patients, the main goal is to restore blood flow and encourage bone regeneration to slow or prevent further damage. While traditional treatments such as drugs and surgery are still common, there is growing interest in using biomaterials to aid bone healing and possibly avoid the need for joint replacement. This article reviews the latest progress of biomaterials for the treatment of osteonecrosis. These materials support bone repair by improving the local environment around bone, influencing cellular behavior, and even promoting gene expression. It also discusses the challenges of transferring these materials from research to clinical practice and examines emerging trends in biomaterials research. For these promising therapies to be more effective in improving outcomes for patients with osteonecrosis, a collaborative multidisciplinary approach will be essential.